A systematic study of the dissolution and relative bioavailability of four ginsenosides in the form of ultrafine granular powder, common powder and traditional pieces of Panax quinquefolius L, in vitro and in beagles. (5th June 2016) - Chen, Sha; Xu, Hao-Qi; Zhang, Jun; Wang, Cai-Xia; Liu, Jun-Qiu; Peng, Li-Hua; Cheng, Jin-Le; Liu, An
Abstract: Ethnopharmacological relevance: Panax quinquefolius L (PQ), also known as American ginseng, has been used as a medicinal herb for thousands of years in the Far East, which was wildly used actively in healing the cardiovascular, endocrine and immune systems, in supporting chemoprevention of cancer. Materials and methods: An integrated, rapid, sensitive and reliable UHPLC-ESI-QQQ MS/MS method was validated and successfully applied in a pharmacokinetics study in which four representative ginsenosides were measured in beagle plasma following oral administration of Panax quinquefolius L (PQ) in the form of ultrafine granular powder, standard powder and an extract. Results: Two paired ions ([M+Na] + in the positive MS process, and two characteristic ions [Q3 ] + in the positive MS/MS process) of the target compounds were optimized and selected for improved qualitative and quantitative analysis of ginsenosides in beagle plasma. The relative bioavailability of the target ginsenosides in these three formulations was measured by the pharmacokinetic parameters, including C max, T max, AUC0−∞ and so on. The ultrafine granular powder had the highest bioavailability, as well as the greatest extent of and fastest dissolution in vitro . Conclusion: Our results show that improved formulations of PQ could facilitate the dissolution and promote absorption of the important compounds it contains. Graphical abstract: